2014
DOI: 10.1039/c4cc06943a
|View full text |Cite
|
Sign up to set email alerts
|

Directed one-pot syntheses of crown ether wheel-containing main chain-type polyrotaxanes with controlled rotaxanation ratios

Abstract: The directed synthesis of main chain-type polyrotaxanes possessing crown ether wheels was successfully achieved through two methods, A and B. Method A involved the direct wheel threading of poly(sec-ammonium salt) followed by end-capping with a bulky group, while method B utilized polyaddition of a pseudo[2]rotaxane monomer to facilitate the control of the structure, i.e. the rotaxanation ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…
Macromolecular [2]

rotaxanes comprising apolymer axle and crowne ther wheel were synthesized to evaluate the effect of component mobility on the properties of the axle polymer,e specially its crystallinity.L iving ring-opening polymerization of d-valerolactone with ap seudorotaxane initiator with ahydroxy group at the axle terminus was followed by endcapping with abulky isocyanate.This yielded macromolecular [2]rotaxanes (M2Rs) possessing polyester axles of varying molecular weights.The crystallinity of the axle polymers of two series of M2Rs,with either fixedand movable components,was evaluated by differential scanning calorimetry.T he results revealed that the effect of component mobility was significant in the fixedand movable M2Rs with acertain axle length, thus suggesting that the properties of the axle polymer depend on the mobility of the polyrotaxane components.

Polyrotaxanesareattractingconsiderableattentionowingto their wide application range derived from the structural characteristics of their topological bonding and the dynamic nature of their components. [4] These results demonstrate that the wheel component of polyrotaxanes clearly affects the properties of the axle polymer,especially the phase-transition temperature.H owever,d etailed elucidation of the effect of the rotaxane structure remains difficult. Theresearch groups of Beckham and Gibson independently reported that melting (T m )and glass transition (T g )temperatures of the axle polymers of main-chain-type polyrotaxanes are lowered in the presence of wheel components.

…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…
Macromolecular [2]

rotaxanes comprising apolymer axle and crowne ther wheel were synthesized to evaluate the effect of component mobility on the properties of the axle polymer,e specially its crystallinity.L iving ring-opening polymerization of d-valerolactone with ap seudorotaxane initiator with ahydroxy group at the axle terminus was followed by endcapping with abulky isocyanate.This yielded macromolecular [2]rotaxanes (M2Rs) possessing polyester axles of varying molecular weights.The crystallinity of the axle polymers of two series of M2Rs,with either fixedand movable components,was evaluated by differential scanning calorimetry.T he results revealed that the effect of component mobility was significant in the fixedand movable M2Rs with acertain axle length, thus suggesting that the properties of the axle polymer depend on the mobility of the polyrotaxane components.

Polyrotaxanesareattractingconsiderableattentionowingto their wide application range derived from the structural characteristics of their topological bonding and the dynamic nature of their components. [4] These results demonstrate that the wheel component of polyrotaxanes clearly affects the properties of the axle polymer,especially the phase-transition temperature.H owever,d etailed elucidation of the effect of the rotaxane structure remains difficult. Theresearch groups of Beckham and Gibson independently reported that melting (T m )and glass transition (T g )temperatures of the axle polymers of main-chain-type polyrotaxanes are lowered in the presence of wheel components.

…”
mentioning
confidence: 76%
“…[1] Thes ynthesis and applications of primarily main-chain-type polyrotaxanes [2] have been extensively studied for two decades.H owever,t here are few reports that describe the relationship between the chemical structure and properties of polyrotaxanes.P articularly,t he effect of the presence of awheel component on the properties of the axle polymer is an ongoing investigation. [4] These results demonstrate that the wheel component of polyrotaxanes clearly affects the properties of the axle polymer,especially the phase-transition temperature.H owever,d etailed elucidation of the effect of the rotaxane structure remains difficult. [3] We also reported that the T g values of polyrotaxane axle polymers decrease with increasing numbers of wheel components.M oreover,t he interaction between the axle and wheel components also affects the T g of polyrotaxane.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Due to the interesting molecular topologies, one could expect polyrotaxanes to exhibit unique properties and morphological structures. Their properties have been investigated in some extents with respect to the effects of rotaxanes . However, their morphological structures and characteristics are rarely examined.…”
Section: Characteristics Of Pvl and Its Axles Bearing Movable And Fixmentioning
confidence: 99%
“…We also reported that the T g values of polyrotaxane axle polymers decrease with increasing numbers of wheel components. Moreover, the interaction between the axle and wheel components also affects the T g of polyrotaxane . These results demonstrate that the wheel component of polyrotaxanes clearly affects the properties of the axle polymer, especially the phase‐transition temperature.…”
Section: Figurementioning
confidence: 99%